Results of a Global Survey of Experts to Categorize the Suitability of Interventions for Inclusion in School Health Services - Plummer, Mary Louisa; Chan, Ace; Kohl, Kid; Taylor, Ashley B.; Baltag, Valentina; Saewyc, Elizabeth; Ross, David Anthony (Journal of adolescent health, 2021)
This global survey of experts assessed the suitability of different health-related interventions for inclusion in school health services (SHSs) to inform development of the World Health Organization global guideline on SHSs. A review of 138 global World Health Organization publications identified 406 health service interventions for 5- to 19-year-old individuals. These were consolidated, pretested, and pilot-tested in a questionnaire as 86 promotion, prevention, care, or treatment interventions. A total of 1,293 experts were identified through purposive sampling of journal databases and professional networks. In July 2019, experts were invited to complete the questionnaire online in Arabic, Chinese, English, French, Russian, or Spanish. Respondents categorized each intervention as essential, highly suitable, suitable, or unsuitable in SHSs (everywhere or in certain geographic areas only). They could also suggest interventions. Interventions categorized most often as “Essential in SHSs everywhere” (70%–80%) are related to health promotion and health education. Clinical interventions categorized most often in this way (60%–68%) are related to immunization, screening, assessment, and general care. Interventions categorized most often as “Essential in SHSs in certain geographic areas only” (27%–49%) are related to immunization, mass drug administration, and health promotion. Interventions categorized most often as “Unsuitable in SHSs anywhere” (12%–14%) are related to screening of noncommunicable conditions. There were no important regional differences. Of 439 respondents from 81 countries, 188 suggested 378 additional interventions. Question order effect and/or purposive sampling biases may have influenced both quantitative and qualitative results for different types of intervention. Favorable responses to almost all interventions supported their World Health Organization guideline inclusion but provided little guidance for intervention prioritization.